Self-degradation in Filipino Catholic Spirituality: Its Expressions, Causes, and Healing - Acebedo, Baltazar (The PASCHR journal, 2021)
This study entitled "Self- Degradation in Filipino Catholic Spirituality: Its Expressions, Causes, and Healing" employed a socio-historical analysis of the Philippine colonial past and critical reading of Ecclesia in Asia to understand the possible causes of self-degradation in Filipino Catholic spirituality, both in the past and the present. The Feast of the Black Nazarene and Good Friday are Filipino Catholic celebrations that impress the international community’s amazement and confusion. Some think that these celebrations depict a distinct character of Filipino Catholic spirituality in contrast with other Catholic spiritualities globally. While some regard them as manifestations of faith, others consider it on the edge of heresy and a hangover of Philippine pre-colonial animism. Even the Philippine Catholic Church finds it difficult to make sense of this character of Filipino Catholic spirituality. Hence, the questions that revolve around these Filipino Catholic traditions are intimately connected to the issue of how a Filipino understands her culture.